Legislative gridlock and stock return dispersion around roll-call votes - Cheng, Mengyao (Journal of Banking & Finance, 2022)
This study examines whether and how legislative gridlock in Congress affects legislative uncertainty. Results show that legislative gridlock increases cross-sectional dispersion in returns on individual stocks and portfolios over short windows around roll-call votes on Congressional bills. The effect of gridlock is beyond political polarization, Presidential ideology, unified versus divided governments, economic recession, policy uncertainty (Baker et al., 2016), and macroeconomic uncertainty (Jurado et al., 2015). Greater legislative uncertainty is associated with higher bond yield and lower likelihood of seasoned equity offerings and analyst recommendations. The effect of gridlock depends on industry and firm characteristics, as well as political polarization and Presidential ideology. Overall, legislative gridlock increases legislative uncertainty as reflected in cross-sectional dispersion in stock returns.